Comparing Social Network Structures Generated through Sociometric and Ethnographic Methods. Issue 4 (November 2020) - Ready, Elspeth; Habecker, Patrick; Abadie, Roberto; Dávila-Torres, Carmen A.; Rivera-Villegas, Angélica; Khan, Bilal; Dombrowski, Kirk
Social connections between individuals are often an important source of information for both quantitative and qualitative anthropological research. Here, we seek to understand the relative strengths and weaknesses of sociometric and ethnographic representations of social connections. We do this by comparing network data collected using a sociometric technique (a name generator) with a network drawn by project ethnographers representing their understanding of social structure in the study population. We find many similarities in the two networks, but they offer somewhat different perspectives into the local social structure. Although the ethnographic network is shaped by the ethnographers' deeper knowledge of a subset of network members, individuals with high degree (but not betweenness) in the sociometric network are generally present in the ethnographic network. The ethnographers' interpretation of the factors that lead to high degree centrality in the network is broadly accurate. However, the sociometric network is characterized by a high level of transitivity not seen in the ethnographic network. We consider the importance of the differences we observe for ethnographic practice.